The case for a modern multiwavelength, polarization-sensitive LIDAR in orbit around Mars. (March 2015) - Brown, Adrian J.; Michaels, Timothy I.; Byrne, Shane; Sun, Wenbo; Titus, Timothy N.; Colaprete, Anthony; Wolff, Michael J.; Videen, Gorden; Grund, Christian J.
Abstract: We present the scientific case to build a multiple-wavelength, active, near-infrared (NIR) instrument to measure the reflected intensity and polarization characteristics of backscattered radiation from planetary surfaces and atmospheres. We focus on the ability of such an instrument to enhance, potentially revolutionize, our understanding of climate, volatiles and astrobiological potential of modern-day Mars. Such an instrument will address the following three major science themes, which we address in this paper: Science Theme 1. Surface . This would include global, night and day mapping of H2 O and CO2 surface ice properties. Science Theme 2. Ice Clouds . This would including unambiguous discrimination and seasonal mapping of CO2 and H2 O ice clouds. Science Theme 3. Dust Aerosols . This theme would include multiwavelength polarization measurements to infer dust grain shapes and size distributions. Highlights: We present the scientific rationale for a multi-wavelength, polarization sensitive lidar to be placed in orbit around Mars. Scientific questions focus on the Martian climate and modern-day interactions between surface, ice clouds and dust aerosols. What we would learn about volatile transport and deposition has implications for past, present and future life on Mars.